CURRICULUM AND COMPETENCE: EVALUATING PAKISTAN'S EDUCATIONAL FRAMEWORK AGAINST GLOBAL STANDARDS - Dr. Muhammad Nisar; Dr. Muhammad Naseer U Din; Dr. ShahJehan (Journal of Religion and Society, 2025)
This article provides a critical analysis of Pakistan's educational framework, evaluating its effectiveness and competence against global standards. It identifies key areas where Pakistan's educational system aligns with or diverges from international best practices in curriculum development and educational outcomes. The study focuses on curriculum content, pedagogical approaches, assessment methods, and the integration of technology, comparing these elements with systems in OECD countries and emerging economies. The research methodology includes a review of existing literature, policy analysis, and comparative case studies of educational practices in selected countries. The findings highlight significant gaps in Pakistan's educational system, particularly in areas like critical thinking, creativity, and problem-solving skills. The study also examines the impact of socio-economic factors on educational access and quality, revealing disparities that affect educational equity and inclusion. Furthermore, the paper discusses the challenges faced by Pakistan in implementing educational reforms, such as resistance to change within institutional frameworks, lack of professional development for teachers, and inadequate infrastructure. Recommendations for aligning Pakistan’s educational system with global standards include curriculum modernization, teacher training programs, policy reforms, and increased investment in educational technology. In conclusion, "Curriculum and Competence: Evaluating Pakistan's Educational Framework Against Global Standards" offers a comprehensive overview of the strengths and weaknesses of Pakistan's education system. It provides actionable insights for policymakers, educators, and stakeholders aimed at enhancing the quality and relevance of education in Pakistan to meet global standards. Keywords: Pakistan, Educational Framework, Global Standards, Curriculum Development, Educational Outcomes, OECD, Educational Equity, Pedagogical Approaches, Curriculum Modernization, Educational Reform.